MICROBIAL CONTAMINATION OF ESCHERICHIA COLI IN DIFFERENT TYPES OF FOODS OF ANIMAL ORIGIN - Tsalisa Praba Kusuma; Rasyad Wahyu Mahendra; Resta Lasarika; Aris Renanda Takbir’adha Hardanny; Nur Ika Prihanani (Buletin Veteriner Udayana, 2024)
Animal-based foods are an important source of protein. However, the presence of pathogenic microbes such as Escherichia coli (E. coli) in food products can lead to serious issues concerning food safety and public health. This study aims to provide a literature review on the contamination of E. coli in various animal-based foods, including chicken meat, beef, fish, and milk, with a focus on several factors including the causes of contamination, its impact on food safety, and effective control measures. The research method used is a literature review utilizing various electronic sources. A total of 335 chicken meat samples were tested, with 270 positive and 65 negative results. A total of 73 beef samples were tested, with 63 positive and 10 negative results. A total of 16 fish samples were tested, with 9 positive and 7 negative results. A total of 37 milk samples were tested, with 15 positive and 22 negative results. The overall findings indicate that E. coli contamination in animal-based food products can occur at various stages, from production to distribution. This contamination can lead to foodborne diseases such as diarrhea and more serious gastrointestinal infections, especially in vulnerable populations. Factors such as hygiene and individual behavior, environmental conditions, cleanliness, and unhygienic processing methods are the main causes of the increased risk of contamination. The literature review discusses the importance of implementing food safety standards, biosecurity, and appropriate processing technologies to reduce the risk of contamination. Educating the public and food industry stakeholders on safe food handling practices is crucial in preventing foodborne diseases caused by E. coli.